Research Of Emotional Intelligence Of Chess Teachers And Pupils - Khachatryan, Armine; Sargsyan, Anzhela (Զանգակ հրատ.)
The research relevance is conditioned by the lack of experimental data on the study of the level of emotional intelligence of school teachers and learners of chess. The aim of the research is to identify the level of emotional intelligence of teachers and junior schoolchildren and their manifestation during the teaching and mastering of the “Chess” subjects. In accordance with the purpose of the research, "Happy and sad", "Do you understand emotions by mimics?", "Emotions identification, pupil", "Emotions identification, teacher", N. Holly's intellectual level diagnostic methodologies have been applied. The study results. Summarizing the results of analyses of all the applied methods during this research, it can be concluded that the low indicators of empathy of the teachers, managing emotions of themselves and others affects both the motivation to success of the 3 rd and 4 th grade pupils as well as the negative attitude to obtaining the teacher's appraisal, as a result of which the indicator of a positive attitude towards the teacher of the chess is diminished. The practical significance of the research. Taking into account the data analysis of the results of this study, we suggest providing training program in the chess teachers. The aim is to increase the level of development of chess teachers' emotional intelligence, to develop the ability of schoolchildren to recognize, distinguish and title the emotions of chess classes. The goal is to increase the level of development of chess teachers' emotional intelligence, to develop the ability to recognize, distinguish and title the emotions of schoolchildren in chess classes.
Keywords: Psychology